2013
DOI: 10.1137/080733140
|View full text |Cite
|
Sign up to set email alerts
|

Diametral Pairs of Linear Extensions

Abstract: Given a finite poset P, we consider pairs of linear extensions of P with maximal distance, where the distance between two linear extensions L 1 , L 2 is the number of pairs of elements of P appearing in different orders in L 1 and L 2 . A diametral pair maximizes the distance among all pairs of linear extensions of P. Felsner and Reuter defined the linear extension diameter of P as the distance between a diametral pair of linear extensions.We show that computing the linear extension diameter is NPcomplete in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Then (3) follows from last two equalities and ( 1). ( 4) follows by duality from (2). ✷ Proof (of Theorem 3.1).…”
Section: From Valuations To Realizersmentioning
confidence: 94%
See 1 more Smart Citation
“…Then (3) follows from last two equalities and ( 1). ( 4) follows by duality from (2). ✷ Proof (of Theorem 3.1).…”
Section: From Valuations To Realizersmentioning
confidence: 94%
“…The construction of a complete valuation on a lattice from a realizer of the underlying poset, that we'll give in Section 4, has some points in common with the construction of a pair of diametral linear extensions, as defined, for instance, in [2] , [4] , [6]. The order induced by a complete valuation, which is lexicographic with respect to one of the linear extensions of the poset, is a linear extension of the lattice; the diametrally opposite linear extension would be given by another complete valuation, whose weight function counts chains in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%
“…It is known to be N P-complete to decide whether an ordered set can be altered to be two-dimensional by inserting k pairs [1]. Hence, we propose an algorithm that tackles the problem for approximating the corresponding optimization problem.…”
Section: Such An Extension Always Exists: a Linear Extension Of Dimen...mentioning
confidence: 99%
“…The transitive incomparability graph of this ordered set has 206 vertices. By removing pairs (5,9), (3,13), (6,15), (17,15), (5,15), (5,13), (11,10), (9,6), (5,6), (4,15), (1,8), (3,15), (11,12), (2,8), (11,7), (0,15), (1,16), the transitive incomparability graph of this ordered set becomes bipartite. However, if we once again compute the transitive incomparability graph of the new ordered set, we see that it is not bipartite, i.e., the new ordered set is once again not two-dimensional.…”
Section: Bipartite Subgraph Is Not Sufficientmentioning
confidence: 99%
“…More generally, in [5], Felsner and Massow give a polynomial-time algorithm for computing the linear extension diameter of downset lattices of 2-dimensional posets; an analysis of their proof shows that RR(P) ≥ 1/2 for all such posets. By contrast, Brightwell and Massow [4] showed that it is NPcomplete to compute the linear extension diameter of an arbitrary poset.…”
Section: Introductionmentioning
confidence: 98%